Terapia delle psicosi e trattamento comunitario: un dibattito - Vari, Autori (Il sogno della farfalla, 2018)
Within the debate that took place during a refresher course, “Therapy for psychosis and community-based management”, which was held in Rome, a few aspects relevant to the practice of therapeutic communities were expounded. Amongst these, there were: the relationship between psychotherapy and other activities, the presence of the psychotherapist outside the psychotherapeutic setting, the relationship with the relatives of the patients.